2021
DOI: 10.3991/ijet.v16i04.18577
|View full text |Cite
|
Sign up to set email alerts
|

Mobile and Web-Based Support in Overcoming Behavioral Difficulties of Adolescents

Abstract: A significant proportion of adolescents and young adults experience behavioral difficalties as they grow up. Minor disorders without control and relief can cause significant psychological problems and disorders or form dangerous life paths for a teenager. Mobile devices and applications have been actively used for over a decade to monitor and provide psychological assistance to adolescents. The aim of this study was to identify the level of effectiveness of the impact of mobile and online support for adolescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…These findings align with the studies that found teachers' support buffers behavioral difficulties, increases competence, and reduces attachment issues. [120][121][122] Teachers' support and good quality child-teacher interactions reduce aggression and improve self-regulation. 123…”
Section: Support From Teachers Subscalementioning
confidence: 99%
“…These findings align with the studies that found teachers' support buffers behavioral difficulties, increases competence, and reduces attachment issues. [120][121][122] Teachers' support and good quality child-teacher interactions reduce aggression and improve self-regulation. 123…”
Section: Support From Teachers Subscalementioning
confidence: 99%
“…In recent years, psychological problems of college students have increasingly attracted attention from various sectors of society [1][2][3]. In modern society, college students are faced with enormous pressure in their studies, daily life, and employment, which easily leads to their psychological problems [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%